Citizenship in the European Union - Manuel Méndez Santamaría (ADIDE Federación, 2008)
The double purpose of this article is first to clarify the concept of citizenship as intended in the European Union and, second, to encourage society in our country -particularly the segment of society involved in education- to carry out a serious reflection on it, made in an objective manner and in a constructive focus, far away from stereotypes which support vested interests that could occasionally cause social divisions.